DEVELOPING CRITICAL THINKING SKILLS OF PRIMARY SCHOOL STUDENTS THROUGH INDEPENDENT CURRICULUM LEARNING - Irwan Irwan; Arnadi; Aslan Aslan (CV. ADIBA AISHA AMIRA, 2024)
The development of critical thinking skills among elementary school students plays an important role in preparing the younger generation to face the challenges of the fourth industrial revolution era. The method used is a literature study on this theme. The results of the study revealed that Merdeka Belajar Curriculum provides ample space to improve students' critical thinking skills through flexible learning, focusing on students, and closely related to context. Effective strategies include project-based learning, collaborative problem solving, and technology integration in the learning process. However, the research also identified challenges such as the need for intense enrichment of teacher competencies and adaptation of assessment methods to appropriately measure critical thinking skills. In conclusion, Merdeka Belajar Curriculum has great potential to improve the critical thinking skills of primary school students, but this achievement is highly dependent on careful implementation along with comprehensive support from all education stakeholders. Recommendations for further studies include long-term studies on the long-term impact of this curriculum on the development of students' critical thinking skills and the exploration of new assessment models that are in line with the objectives of the Merdeka Belajar Curriculum